PERAN TEKNOLOGI KOMUNIKASI DALAM RANTAI NILAI PEDAGANG DI PASAR TRADISIONAL - Popy Rufaidah (Fakultas Seni Rupa dan Desain ITB, 2008)
Communication technology is one of the communication tools which has important role in human life. The used of it exists among people of all ages and of all social classes. Small scale entrepreneurs such as traders in traditional markets use communication technology for example cellular phones as tools to communicate among their clients to facilitate their commercial activities in their value chain. The study examined traders in 15 traditional markets in Bandung area. The result of the study showed that communication technology is one of the tools which have changed the culture of traders' society in the traditional markets. The traders used communication technology in its value chain particularly for communicating their business to among of their traders in the markets and to their suppliers. The study recommended, firstly, the importance of providing accessible and economical communication technology for micro scale entrepreneurs such as traders at the traditional markets. Secondly, government collaborates with national telecommunication cellular providers to support the economic growth of the small scale traders particularly the traders with micro scale in the traditional markets.